Determinants of debt management among fresh graduates - Nurul Atahsa Shahira Masrom; Iffatul Widad Mohd Fauzi; Nurul Fazira Mohd Nazri; Masnita Misiran; Zahayu Md Yusof (Penerbit Universiti Kebangsaan Malaysia, 2022)
Fresh graduates in Malaysia appear to be overwhelmed by money, falling into debt, and jeopardizing their financial contentment. In this study, we aim to identify the determinant of debt management among fresh graduates and the relationship between debt management and gender, ethnicity, education loan, car, saving ratio, debt to income ratio, and financial skills by using multiple regression analysis. Finding suggests that fresh graduates with good financial skills are more likely to have good debt management, and women are found to manage debt better than men, thus the need to include financial education at the university level to prepare this age group before they enter the job market.